2016
DOI: 10.1111/1753-6405.12391
|View full text |Cite
|
Sign up to set email alerts
|

The economic feasibility of price discounts to improve diet in Australian Aboriginal remote communities

Abstract: Objective: To estimate the cost-effectiveness of fiscal measures applied in remote community food stores for Aboriginal Australians.Methods: Six price discount strategies on fruit, vegetables, diet drinks and water were modelled. Baseline diet was measured as 12 months' actual food sales data in three remote Aboriginal communities. Discount-induced changes in food purchases were based on published price elasticity data while the weight of the daily diet was assumed constant. Dietary change was converted to cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…The literature to inform food pricing policy has grown rapidly since the implementation of these policies, including in relation to magnitude, 10–13,37 which in addition to the finding related to a ‘threshold value’ of this study, would be valuable to informing the design of future food pricing policy. The feasibility and sustainability of these would need to be considered by the implementing organisation or store 9 . Robust evaluation of natural experiments, as presented here, is vital to inform policy within an organisation or store and to contribute to broader policy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature to inform food pricing policy has grown rapidly since the implementation of these policies, including in relation to magnitude, 10–13,37 which in addition to the finding related to a ‘threshold value’ of this study, would be valuable to informing the design of future food pricing policy. The feasibility and sustainability of these would need to be considered by the implementing organisation or store 9 . Robust evaluation of natural experiments, as presented here, is vital to inform policy within an organisation or store and to contribute to broader policy.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling studies suggest that fruit and vegetable subsidies (i.e. price reduction or food at no cost) can have positive impacts on dietary intake, health outcomes and potential cost benefits, including in remote Aboriginal communities 8,9 . Three supermarket‐based randomised controlled trials of price discounts on healthier foods, 10 fruit and vegetables, 11 and fruit, vegetables and beverages, 12 reported a positive impact on purchases of targeted foods, with the exception of bottled water and low‐calorie beverages 12 .…”
mentioning
confidence: 99%
“…directly collected checkout scanner data, commercially available data sets and grocery receipts) have been used to monitor the effectiveness of interventions in a variety of types of retail food stores, [9][10][11][12] including a number of recent small-store studies. [13][14][15][16][17] Together, these studies suggest that sales data can actually be used in the design of retail food interventions. For example, Foster and colleagues 9 found that low-cost strategies focussed on improving product availability and placement enhanced sales of some foods and beverage categories (milk, water, frozen meals) but not others (regular soda, diet soda, cereal).…”
Section: Introductionmentioning
confidence: 93%
“…10,12,16 Related mixed retail interventions (not explicitly "healthy corner stores"), including availability, pricing and education, have increased healthy food purchasing and consumption. 18,19 Reviews of corner store research suggest areas for methodological improvement; 12,16 newer intervention studies 14,15,19,21 have prioritized causal evaluation, and use of objective sales data to measure impact. Of note, financial performance indicators have rarely been measured in public health retail studies, despite their importance for business.…”
Section: Healthy Corner Stores: a Health-promoting Intervention Modelmentioning
confidence: 99%